2007
DOI: 10.1093/ps/86.4.673
|View full text |Cite
|
Sign up to set email alerts
|

Developmental Changes of Plasma Insulin, Glucagon, Insulin-like Growth Factors, Thyroid Hormones, and Glucose Concentrations in Chick Embryos and Hatched Chicks

Abstract: Developmental hormonal changes in Cobb 500 chick embryos and hatched chicks were determined by measuring plasma insulin, glucagon, insulin-like growth factor (IGF)-I, IGF-II, triiodothyronine, thyroxine, and glucose concentrations at different ages of embryogenesis and posthatch development. Plasma samples were obtained daily from 10 d of embryogenesis (10E) through 13 d posthatch and also at 17 and 21 d posthatch. A significant increase in plasma insulin was observed with increasing age from 10E to hatch. Pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

15
80
3
4

Year Published

2009
2009
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 105 publications
(102 citation statements)
references
References 28 publications
15
80
3
4
Order By: Relevance
“…Plasma IGF-I is detectable as early as embryonic d 10, it increases until a plateau is reached from embryonic d 13 to d 18, and it decreases before hatching (Lu et al, 2007). In the present study, the changes of plasma IGF-I levels during the embryonic period are similar to those of Lu et al (2007). Besides, we observed that plasma IGF-I also dramatically increased and reached a plateau with age after hatching.…”
Section: Discussionsupporting
confidence: 76%
See 3 more Smart Citations
“…Plasma IGF-I is detectable as early as embryonic d 10, it increases until a plateau is reached from embryonic d 13 to d 18, and it decreases before hatching (Lu et al, 2007). In the present study, the changes of plasma IGF-I levels during the embryonic period are similar to those of Lu et al (2007). Besides, we observed that plasma IGF-I also dramatically increased and reached a plateau with age after hatching.…”
Section: Discussionsupporting
confidence: 76%
“…The decline in plasma GH preceded the decline in circulating IGF-I, suggesting that IGF-I and GH are weakly coupled during late posthatch development of the chicken. Besides, we found a significant decrease in plasma IGF-I in day-old chicks, though Lu et al (2007) reported that plasma IGF-I levels increased in day-old chicks. Feed intake can decrease plasma levels of IGF-I in day-old chicks (Guernec et al, 2003), which might be the reason for the dramatically decrease in plasma IGF-I of day-old broilers in the current study.…”
Section: Discussioncontrasting
confidence: 50%
See 2 more Smart Citations
“…Thyroid hormones especially T 3 have a multiple effects on vertebrate metabolism and development. A T 3 regulate basal metabolic rate and are essential for the maintenance and constant body temperature and protein and lipid metabolism (Collin et al, 2005;Lu et al, 2007). Also during development, T 3 stimulate both growth and differentiation of organs, their action can be direct, indirect or permissive (Zation et al, 1993).…”
mentioning
confidence: 99%